NCCTG N0543 (Alliance): A Phase II Trial of Pharmacogenetic-Based Dosing of Irinotecan, Oxaliplatin, and Capecitabine as First-Line Therapy for Advanced Small Bowel Adenocarcinoma - McWilliams, Robert R. (Cancer, 2017)
BACKGROUND: Oxaliplatin in combination with either 5-fluorouracil or capecitabine is commonly used as first line therapy for small bowel adenocarcinoma. The addition of irinotecan improves survival in other gastrointestinal tumors but at the cost of hematologic toxicity. We performed a phase II, cooperative group study (NCCTG N0543, Alliance) using genotype-dosed capecitabine, irinotecan, and oxaliplatin (gCAPIRINOX), with dosing assigned based on UGT1A1 genotype in order to 1) test whether the addition of irinotecan would improve outcomes and whether 2) UGT1A1 genotype-based dosing could optimize tolerability. METHODS: Previously untreated patients with advanced small bowel adenocarcinoma received irinotecan (day 1), oxaliplatin (day 1), and capecitabine (days 2–15) in a 21-day cycle and were dosed with gCAPIRINOX according to UGT1A1*28 genotypes (6/6, 6/7, and 7/7). RESULTS: 33 pts (17-6/6, 10-6/7, 6-7/7) were enrolled [73% male, mean age 64 (range 41–77)] from October 2007 to November 2013. Location of primary tumor included: duodenum (58%), jejunum (30%), and ileum (9%). The regimen yielded a confirmed response rate of 37.5% (95% CI 21–56) with median progression-free survival of 8.9 months and median overall survival of 13.4 months. Neither hematologic toxicity (grade 3+ 52.9%, 30.0%, 33.3%, respectively) nor tumor response rate (41.2% 33%, 33%) differed significantly by UGT1A1 genotype (6/6, 6/7, and 7/7 groups). CONCLUSIONS: UGT1A1 genotype-directed dosing (gCAPIRINOX) is feasible with favorable rates of hematologic toxicity compared with prior three drug studies in unselected patients. Larger studies would be needed to determine comparability to CapeOx alone or if response/toxicity differs among genotypes.